Analisis SWOT dalam Strategi Penguatan Komoditas Salak sebagai Produk Unggulan Tapanuli Selatan - Nur Adawiyah Harahap; Fitri Noviyanti Munthe; Karina Zahra; Sumila Sari (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to formulate a procurement strategy for salak commodities as a superior product of South Tapanuli Regency through SWOT analysis. Salak commodities were chosen because they consistently show Location Quotient (LQ) values ​​above 1 in 2021–2024, indicating comparative advantage and export potential. The study uses a qualitative descriptive approach with secondary data from BPS, government reports, and previous studies. SWOT analysis is used to identify strengths, weaknesses, opportunities, and threats in the development of salak, especially canned salak product innovation. The results of the study show that South Tapanuli salak has advantages in terms of production, variety quality, and processed product potential, but still faces obstacles in downstreaming innovation and export market access. The transformation strategy is focused on developing new salak-based products, increasing the capacity of MSMEs, and optimizing market promotion and partnerships. This study recommends strengthening synergy between the government, business actors, and farmers to realize salak as a competitive and sustainable export commodity.